Retrospective analysis of survival after resection of pancreatic renal cell carcinoma metastases - Rückert, Felix; Ollmann, David Johannes; Lietzmann, Anja; Birgin, Emrullah; Téoule, Patrick; Wilhelm, Torsten (International journal of surgery, 2016)
Introduction: Previous reports showed an excellent survival for patients after resection of pancreatic metastases from renal cell cancer (pRCC) and reported several predictive factors. This study aims to give more evidence to reported risk factors by analyzing a large cohort of patients with pancreatic resection due to pRCC. Patients and methods: We retrospectively analyzed all pancreatic resections due to pRCC between January 1993 and October 2014 in two German pancreatic surgery centers. Predictive factors were analyzed using the chi square test. Results: Surgery was performed in 40 patients. Mean survival after resection was 147.9 months (SD 25.6 months). No predictive factors for survival were identified. Pathological examination showed that five out of 21 patients with examined peripancreatic lymph nodes had lymph node metastases. Conclusions: Although our analysis comprised the biggest cohort of patients with pRCC it rendered no significant predictor for survival. This might be due to the overall excellent prognosis of study patients and the relatively rare condition with a limited number of patients. Several patients had lymph node metastases. Therefore lymphadenectomy should be considered in pRCC resection if the health condition of the patient permits this. By this more aggressive approach to pRCC, a better prognosis after resection might be achieved.
Gesehen am 06.02.2019
Available online 29 December 2015